Trajectory of low-density lipoprotein cholesterol in patients with chronic kidney disease and its association with cardiovascular disease - Wang, Shih-Wei; Li, Lung-Chih; Fu, Chung-Ming; Lee, Yueh-Ting; Kuo, Hsiao-Ching; Hsu, Chien-Ning (Frontiers in Cardiovascular Medicine, 2022)
Background: The role of longitudinal temporal trends in LDL-C in cardiovascular disease (CVD) in patients with chronic kidney disease (CKD) and diabetes is unclear. This study categorized the long-term LDL-C trajectory and determined its association with the incidence of atherosclerotic CVD in patients with CKD according to diabetes status and estimated glomerular filtration rate (eGFR). Methods: The risk of atherosclerotic CVD was estimated in 137,127 Taiwanese patients with CKD using six LDL-C trajectory classes determined by the latent class mixed model as optimal, near optimal, above optimal, borderline, sustained high, and declined high over 5 years. Results: The risk of CVD was higher in the sustained high LDL-C (>160 mg/dL over time; adjusted hazard ratio [aHR] = 1.68, 95% CI = 1.45–1.94), declined high LDL-C (>160 to <100 mg/dL; aHR = 1.23, 95% CI = 1.11–1.38), and borderline LDL-C (approximately 140 mg/dL over time; aHR = 1.16, 95% CI = 1.07–1.26) groups than in the optimal LDL-C group (<100 mg/dL over time). There was no such association in patients with an eGFR <15 mL/min/1.73 m2. Persistent diabetes was associated with a 1.15–2.47-fold increase in CVD in patients with high LDL-C (120 mg/dL). Conclusions: The LDL-C trajectory pattern was associated with the phenotype of CVD risk. The degree of risk varied according to eGFR and diabetes status. A stable low LDL-C over time was potentially beneficial for prevention of CVD. Intensive lipid management and periodic assessment of LDL-C is essential to reduce the risk of CVD in patients with CKD and diabetes.